Rapid flow diagnostics for prototyping of reservoir concepts and models for subsurface CO2 storage. (March 2023) - Petrovskyy, D.; Jacquemyn, C.; Geiger, S.; Jackson, M.D.; Hampson, G.J.; Machado Silva, J.D.; Judice, S.; Rahman, F.; Costa Sousa, M.
Highlights: Intuitive workflow for prototyping broad range of reservoir concepts for CCS. Flow diagnostics approximate dynamic behaviour of CO2 on the fly. Easy manipulation of injection wells through drag-and-drop. Fast screening reservoir models prior to detailed CCS simulations. RRM software available as open source. Abstract: Sketch-based interface and modelling is an approach to reservoir modelling that allows rapid and intuitive creation of 3D reservoir models to test and evaluate geological concepts and hypotheses and thus explore the impact of geological uncertainty on reservoir behaviour. A key advantage of such modelling is the quick creation and quantitative evaluation of reservoir model prototypes. Flow diagnostics capture key aspects of reservoir flow behaviour under simplified physical conditions that enable the rapid solution of the governing equations, and are essential for such quantitative evaluation. In this paper, we demonstrate a novel and highly efficient implementation of a flow diagnostics framework, illustrated with applications to geological storage of CO2 . Our implementation permits 'on-the-fly' estimation of the key reservoir properties that control CO2 migration and storage during the active injection period when viscous forces dominate. The results substantially improve the efficiency of traditional reservoir modelling and simulation workflows by highlighting key reservoir uncertainties that need to be evaluated in subsequent full-physics reservoir simulations that account for the complex interplay of viscous, gravity, and capillary forces. The methods are implemented in the open-source Rapid Reservoir Modelling software, which includes a simple to use graphical user interface with no steep learning curve. We present proof-of-concept studies of the new flow diagnostics implementation to investigate the CO2 storage potential of sketched 3D models of shallow marine sandstone tongues and deep water slope channels.